2013
DOI: 10.1177/0260106013506666
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational healing

Abstract: Although our continuing evolution can never achieve our perfection, we long for our children's birth and health to be near-perfect. Many children are born healthy, though fewer than is possible. Birthing and health rapidly improved generally due to modern housing, sanitation and medicine, as well as birth interventions. Arguably interventions have exceeded the optimal level, without enough regard for natural physical and intuitive resources. Conception, often too easy, receives too little personal preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…In a US study of linked electronic health records of girls (aged 9 to 17 years) the authors found that mothers’ attitudes about preventative measures such has the Pap test influenced their adolescent daughters update of the HPV vaccine [32]. In turn, individual attitudes and beliefs around health and vaccination are likely to be influenced by parental views and behaviours [33–35]. Unvaccinated participants in our study were more likely to be smokers, were less likely to use contraception and had incomplete attendance at cervical screening, although the latter did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…In a US study of linked electronic health records of girls (aged 9 to 17 years) the authors found that mothers’ attitudes about preventative measures such has the Pap test influenced their adolescent daughters update of the HPV vaccine [32]. In turn, individual attitudes and beliefs around health and vaccination are likely to be influenced by parental views and behaviours [33–35]. Unvaccinated participants in our study were more likely to be smokers, were less likely to use contraception and had incomplete attendance at cervical screening, although the latter did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Stress and sleep disorders are always reported together. Evidences suggest that an exposure to stress [2] and nutrition-rich diet [3] during childhood will determine the emotional regulations in adult life. An exposure to stress during early life likely to increase the corticosterone release even under basal conditions [4].…”
Section: Editorialmentioning
confidence: 99%
“…Physical exercise offers an epigenetic propensity that holds benefits with several health domains, particularly for children and adolescents [59]. Despite issues linked to population selection and quantification of exercise, the overall pattern emerging appears to be a product of the utilization of global methylation as an outcome measure, not depicting changes in DNA methylation at the gene-specific level.…”
Section: Exercise As An Epigenetic Interventionmentioning
confidence: 99%